A new species of Microlaimus de Man 1880 (Nematoda: Microlaimidae) from the Black Sea - Revkova, Tatiana N. (Zootaxa, 2020)
Microlaimus sergeevae sp. n. is described and illustrated from the Crimea shelf of the Black Sea. It is characterized by the 1301–1728 μm long body; cuticle with distinct annuli; spicules 34–37 μm long, curved; gubernacular apophyses 20–25 μm long, surrounding distal end of spicules; criptocyrcular amphidial fovea 7–8 μm in diameter; cervical setae present; four submedian rows of pores spreading along the whole body length, and eight precloacal supplements in males. The new species morphologically resembles M. gerlachi Wieser 1954, M. paraborealis Allgen 1940a and M. kaurii Wieser 1954, but differs from them by the length of cephalic setae, size of the body, presence of cervical setae, shape of the gubernacular apophyses, eight tubular precloacal supplements and submedian rows of pores spreading along the whole body length. M. sergeevae sp. n. differs from M. gerlachi by having a smaller amphidial fovea, shorter spicules and gubernacular apophyses. The new species differs from M. paraborealis by having larger value of c. It differs from M. kaurii by having longer spicules and larger values of c and b.